2022
DOI: 10.1007/s12671-022-01892-w
|View full text |Cite
|
Sign up to set email alerts
|

Being Hopeful and Mindful During Adversity: A Longitudinal Study on College Students’ Adjustment During COVID-19

Abstract: Objectives The current study examined whether hope and mindfulness were associated with changes in two maladjustment measures, internalizing and externalizing behaviors, during the COVID-19 pandemic and tested sense of coherence as a mediator. The salutogenic theory of health, which posits that sense of coherence is central to individuals’ well-being in stressful situations and that individuals derive their sense of coherence from their generalized resistance resources (GRRs), was used to guide th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 59 publications
0
4
0
Order By: Relevance
“…Therefore, the present research investigated how delivering PROSPER‐based interventions via a few technological platforms (e.g., online workshops, smartphone app use, and a combination of those media) can influence well‐being outcomes. As studies have shown that technologically facilitated well‐being interventions such as online workshops with a combination of self‐reflective and interactive activities (Datu et al, 2022), online writing and journaling interventions (Heekerens et al, 2022), and smartphone well‐being apps (Sun et al, 2022) can promote a wide range of positive psychological outcomes, we assessed which mode of intervention delivery might yield stronger impacts on well‐being. Given that having a variety of activities might strengthen the effects of positive psychological interventions (Lyubomirsky & Layous, 2013), we conjectured that combining modes of online workshops supplemented by a smartphone app in the PROSPER‐based intervention framework would enhance pre‐service teachers' psychological outcomes.…”
Section: Theoretical Perspectivementioning
confidence: 99%
“…Therefore, the present research investigated how delivering PROSPER‐based interventions via a few technological platforms (e.g., online workshops, smartphone app use, and a combination of those media) can influence well‐being outcomes. As studies have shown that technologically facilitated well‐being interventions such as online workshops with a combination of self‐reflective and interactive activities (Datu et al, 2022), online writing and journaling interventions (Heekerens et al, 2022), and smartphone well‐being apps (Sun et al, 2022) can promote a wide range of positive psychological outcomes, we assessed which mode of intervention delivery might yield stronger impacts on well‐being. Given that having a variety of activities might strengthen the effects of positive psychological interventions (Lyubomirsky & Layous, 2013), we conjectured that combining modes of online workshops supplemented by a smartphone app in the PROSPER‐based intervention framework would enhance pre‐service teachers' psychological outcomes.…”
Section: Theoretical Perspectivementioning
confidence: 99%
“…Studies have found that higher hope is associated with adaptive behaviors and better outcomes (Bernardo & Sit, 2020; Shanahan et al, 2020; Snyder, 2002). For university students, their level of hope is positively associated with their mental health, resilience, and adjustment (Genç & Arslan, 2021; Rachael, 2020; Sun et al, 2022). Because people with high hopes see things as manageable and meaningful, they may be better able to adjust, especially in the face of adversity.…”
Section: Introductionmentioning
confidence: 99%
“…Darling et al demonstrated that SoC was positively correlated with emotional health and quality of life and inversely correlated with stress from friendships and family issues among university students with distinct gender differences in the associations ( Darling et al , 2007 ). A recent study from China demonstrated that students with higher levels of SoC from a public university had significantly improved resilience against conduct problems, hyperactivity, peer problems, and emotional problems during the COVID-19 pandemic ( Sun et al , 2022 ).…”
Section: Introductionmentioning
confidence: 99%